PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR FISIKA PADA MATERI OPTIKA GEOMETRIS DI KELAS X SEMESTER II MAN 2 TANJUNG PURA T.A 2015/2016 - Utami, Retno; Amdani, Khairul (JURNAL IKATAN ALUMNI FISIKA, 2017)
This study aims to determine the effect of problem based learning model for learning outcomes on geometrical optics material in class X MAN 2 Tanjung Pura T.A 2015/2016. This study is a quasi experimental design with two group pretest-posttest. The population in the study were all students of class X MAN 2 Tanjung Pura. Sampling was done by clusster random sampling by taking two classes, namely class X-2 as the experimental class and class X-3 as the control class numbering, 38 students for grade 39 students for the experimental and control classes. The instrument used to determine student learning outcomes are shaped achievement test essay test with the number of 10 questions. Achievement test in validkan by the validator. Based on the results of hypothesis testing using different test (t-test) results obtained studying the application of problem based learning model has a better improvement than the learning outcomes of students who applied by conventional learning at opyika geometric in class X the second half MAN 2 Tanjung Pura TA 2015 / 2016.